Peningkatan Pengetahuan Dan Konsumsi Sayuran Dan Buah Lokal Pada Anak Sekolah Minggu Jemaat GKI Diaspora Kotayaja Papua - Inggrid Nortalia Kailola; Beatrix I. S. Wanma (Institut Teknologi dan Bisnis Semarang, 2023)
Vegetables and fruit are food sources that are rich in vitamins and minerals. Those are useful to the body because they are important in the body's metabolic processes. Some of the vitamins and minerals found in vegetables and fruits, serve as antioxidants. Lack of consumption of fruits and vegetables can cause the body to experience a deficiency of nutritious substances, which can cause various diseases. This activity aims to provide socialization and understanding to school-age children so they can increase consumption of vegetables and fruits because fruits and vegetables are important to consume from a young age. The student creativity program was held on November 16th 2022 at the GSG the Indonesian Christian Church (GKI) Diaspora Kotaraja Jayapura City, Papua. As many as 18 children participated in this activity. Methods In this activity were: PreTest, Counseling/lectures about the benefits of vegetables and fruit and Post Test. The results of this activity revealed that 88.89% of GKI Diaspora Kotaraja Sunday school children knew about the benefits of local vegetables and fruit, while 11.1% did not know about the benefits of fruits and vegetables.